2012
DOI: 10.1021/ef3003153
|View full text |Cite
|
Sign up to set email alerts
|

Production of High-Grade Carbonaceous Materials and Fuel Having Similar Chemical and Physical Properties from Various Types of Biomass by Degradative Solvent Extraction

Abstract: Eight types of biomass waste samples, microcrystalline cellulose, hemicellulose, and lignin were subjected to a degradative extraction method that treats carbonaceous resources in a non-hydrogen donor at around 350°C. The treated products were separated at 350°C to recover the extract and residue (the latter was termed Residue). The extract was further separated into two fractions: a fraction that precipitates as a solid (termed Deposit(s)) and the soluble fraction (termed Soluble(s)) at room temperature. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…hydroxyl and carboxyl) decomposed and the pore structure of lignite shrunk. Meanwhile, tar that was produced during thermal decomposition of lignite blocked some of the pores and reduced the specific surface area and pore volume of lignite . Some scholars found that the internal pore structure intensity of lignite gradually produces irreversible plastic deformation with the effect of temperature and pressure .…”
Section: Resultsmentioning
confidence: 99%
“…hydroxyl and carboxyl) decomposed and the pore structure of lignite shrunk. Meanwhile, tar that was produced during thermal decomposition of lignite blocked some of the pores and reduced the specific surface area and pore volume of lignite . Some scholars found that the internal pore structure intensity of lignite gradually produces irreversible plastic deformation with the effect of temperature and pressure .…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment that results in the removal of water from biomass is necessary prior to its use in any thermal conversion processes. The degradative solvent extraction (DSE) method has been used successfully to dewater and upgrade low-rank coals [11][12][13][14][15] and biomass [16][17][18] under mild conditions. In DSE, low-rank coal and biomass are treated in a nonpolar solvent in a batch autoclave reactor at around 350 • C under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Water assisted liquefaction requires severe conditions, such as, 50-200 bar pressure and 250-350 °C temperature. An alternative route to process lignocellulosic materials is degradation in none-hydrogen donor organic solvent referred to as liquid phase pyrolysis (LPP) [8][9][10][11][12][13] or degradative extraction (DE) [14][15][16]. According to this method lignocellulosic material is treated at ~350 °C under liquid phase organic solvent and inert atmosphere at relatively low pressure (max.…”
Section: Introductionmentioning
confidence: 99%
“…Gases, mainly CO 2 , and water solubles, non-miscible with the applied solvent, mainly H 2 O, are also formed. Studies report about the use of different organic solvents, such as, mixture of n-alkanes, boiling in the temperature range of 410 and 440 °C [8,9], vacuum gasoline (VGO) that is a mixture of alkanes and aromatics, having a boiling range of 300-580 °C [10,11,13], n-hexane (bp: 69 °C) [12] and 1-methylnaphtalene (bp: 240-243 °C) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%